1977
DOI: 10.1111/j.1432-1033.1977.tb11412.x
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyribonuclease Activity Associated with Adenovirus 5 and 7

Abstract: A DNase activity was found associated with isolated components of adenovirus types 5 and 7. The enzymatic activity was associated with the purified virus and viral components extracted from the soluble material of infected cells. The DNase activity of adenovirus type 5 was maximum at pH 5.5 and 7.0 whereas adenovirus 7 was active only at pH 7.0. Both DNases were shown to be located in the penton fraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1977
1977
1984
1984

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Recently these observations have been confirmed by Marusyk et al [3] and by Cajean-Feroldi et al [4], who reported on an endonuclease in association with pentons of adenovirus types 2, 3, 5, 7, 9, 12, 15 and 16. Under the conditions used by Marusyk et al [3] the endonucleolytic activity caused predominantly single-strand scissions in the DNA substrate.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Recently these observations have been confirmed by Marusyk et al [3] and by Cajean-Feroldi et al [4], who reported on an endonuclease in association with pentons of adenovirus types 2, 3, 5, 7, 9, 12, 15 and 16. Under the conditions used by Marusyk et al [3] the endonucleolytic activity caused predominantly single-strand scissions in the DNA substrate.…”
supporting
confidence: 76%
“…In previous work an endonuclease specific for double-stranded DNA has been described in association with the penton subunit of adenovirus type 2 [l], in extracts of KB cells infected with adenovirus types 2 and 12 and in association with purified preparations of adenovirus [2]. Recently these observations have been confirmed by Marusyk et al [3] and by Cajean-Feroldi et al [4], who reported on an endonuclease in association with pentons of adenovirus types 2, 3, 5, 7, 9, 12, 15 and 16. Under the conditions used by Marusyk et al [3] the endonucleolytic activity caused predominantly single-strand scissions in the DNA substrate.…”
mentioning
confidence: 70%
“…In addition to these endonuclease activities probably coded for by the host genome, an endonuclease specific for double-stranded DNA has been described in association with the penton subunit of Ad 2 (4,5). Marusyk et Abbreviation used: Ad, adenovirus, TCA, trichloroacetic acid; d*G denotes d32P G. C) Information Retrieval Limited 1 Falconberg Court London Wl V 5FG England al (6) and Cajean-Feroldi et al (7) confirmed and extended the observations that the pentons of adenovirus types 2, 3, 5, 7, 9, 12, 15 and 16 were associated with an endonuclease. Under the conditions used by Marusyk et al (6), the penton-associated endonuclease caused predominantly single-strand scissions in the DNA substrate.…”
Section: Introductionmentioning
confidence: 99%